Integrating Health Information Systems: A Critical Appraisal - Monteiro, E. (Methods of Information in Medicine, 2003)
Objectives: The aim of this paper is to critically assess some of the underlying assumptions behind these initiatives and analyze the dominant expressions, forms and mechanisms of integration.Methods: This paper employs a discourse analysis to elicit the notion of integration of information systems and its consequences for electronic patient record systems.Results and Conclusions: An alternative strategy is outlined, encouraging a more decentralized, multi-vocal approach acknowledging the productive role of related and duplicated information and preserving the existing variety of information systems.
Keywords: Health information systems; integration; electronic patient records systems; business process re-engineering (BPR)